Methyl 2, 2‐Difluoro‐2‐(Fluorosulfonyl) Acetate as a Novel Electrolyte Additive for High‐Voltage LiCoO2/Graphite Pouch Li‐Ion Cells. Issue 5 (30th January 2020) - Xiang, Fuyou; Wang, Pipi; Cheng, Hao
Abstract : Herein, a novel sulfone‐based compound, methyl 2, 2‐difluoro‐2‐(fluorosulfonyl) acetate (MDFA) is studied for its effects in improving LiCoO2 /graphite pouch Li‐ion cell performance at high working voltage (4.45 V). Calculations based on density functional theory (DFT) and electrochemical tests reveal that MDFA can be reduced preferentially compared with the electrolyte solvent. It helps form a robust interface film with high lithium‐ion conductivity, which will greatly reduce the interfacial impedance of cells. The pouch cells containing 1 wt% MDFA show excellent discharge performance at low temperature (−10 °C) and such concentration of MDFA can also inhibit the deposition of lithium on the anode. Moreover, this additive can promote stability of cell cycling at high voltage. The overall results indicate that the MDFA is a low‐impedance additive that can be well applied to improve the property of high‐voltage lithium‐ion batteries. Abstract : This novel electrolyte additive seems to construct a uniform solid electrolyte interphase (SEI) layer that allows fast charge transport inside the anode with no Li metal plating on the anode surface, which greatly improve the cells' quick charging performance.